FROM UMMAH TO USERNAME: HOW DIGITAL PLATFORMS RESHAPE ISLAMIC SOLIDARITY AND STRATIFICATION - Khoiruz Zaman, Wahyu; Ansori, Miswan; Saefudin, Ahmad (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
While numerous studies have examined how digital media mediate religious expression, few have addressed how online platforms actively reshape Islamic solidarity while generating new forms of social stratification. Existing literature often highlights da’wah or online communities in general, but rarely connects algorithmic logics, visual aesthetics, and performative religiosity to the transformation of the ummah. This article fills that gap by analyzing hijrah communities, Muslim influencers, and visual Islamic preaching on Instagram and TikTok. Employing qualitative digital ethnography and drawing on Bourdieu’s concepts of habitus, field, and symbolic capital, the study shows that Islamic solidarity is increasingly segmented by algorithmic visibility, symbolic capital, and performative piety. Three key findings emerge: first, solidarity is filtered by digital literacy and visual conformity; second, performative religiosity supplants communal substance; and third, algorithmic logic reinforces symbolic exclusion. The article contributes to debates on Islamic identity, digital religiosity, and representation politics, advocating for more inclusive and ethical digital Islamic spaces.